Energy Transmission and Energy Harvesting via an Electro-Dynamical Transducer - Pechuk, Evgeniy D.; Krasnopolskaya, Tatyana S. (Journal of Vibration Testing and System Dynamics, 2026)
This paper addresses energy transmission via an electro-dynamical transducer from the amplifier and energy harvesting from wave field. In the first case an amplifier is considered as a self-exciting system with a limited power. Electrical current produced by it is converted by the transducer into mechanical force, which leads to vibrations of the base. A mechanical oscillator is mounted on the transducer base. The influence of oscillator vibrations on the formation of the driving force leads to the Sommerfeld --Kononenko effect. Expressions for supplied and consumed powers are shown. The energy harvesting problem is also discussed. The classical results for wave power harvesting by wave energy extractor as a single degree of freedom system are presented in the second considered problem. The example includes an axisymmetric buoy which oscillates and is subjected to its natural hydrostatic restoring force. Main attention is focuses on the values and expressions for the mean powers. The expression for the maximum mean power is given for the considering system.